LINGUOCULTURAL STUDY OF THE LATIN AND GREEK DERIVATIONAL POTENTIAL OF ENGLISH WORD-MAKING ELEMENTS - Saliyeva Surayyo Mansurjanovna (Scholars Digest Publishing, 2023)
This article aims to investigate the Latin and Greek derivational potential of English word-making elements through a linguocultural study. The study will explore the historical and cultural contexts in which Latin and Greek elements were incorporated into the English language, and how they have been used to create new words over time. The methods used in this study include a literature review of relevant linguistic and cultural sources, as well as an analysis of the etymology and semantic structure of English words formed with Latin and Greek elements. The results of this study shed light on the complex relationship between language and culture, and demonstrate the enduring influence of Latin and Greek on the English language. The article concludes with suggestions for further research in this area, and emphasizes the importance of understanding the cultural context of language in order to fully appreciate its richness and diversity.